Galen and the Arabic Reception of Plato's Timaeus - Das, Aileen R. (Cambridge University Press, 2020)
Cover -- Half-title page -- Title page -- Copyright page -- Dedication -- Contents -- List of Figures -- Acknowledgements -- Notes on Texts, Translations, and Transliterations -- List of Abbreviations -- Introduction: Plato's Timaeus as Universal Text -- Chapter 1 Galen and the 'Medical' Timaeus -- Chapter 2 From the Heavens to the Body: Ḥunayn's Ophthalmology -- Chapter 3 Al-Rāzī: The 'Arab Galen' and his Plato, New Disciplinary Ideals -- Chapter 4 Laying Down the Law: Avicenna and his Medical Project -- Chapter 5 Uprooting the Timaeus: Maimonides and the Re-medicalization of Galenism -- Conclusion: Medicine Disciplined -- References -- Index Locorum -- General Index.